Report on Evaluation Study of Small Farmers, Marginal Farmers and Agricultural Labourers Projects 1974-75 - Planning Commission (Planning Commission, 1979)
The Scheme of Small Farmer. Development Agencies (SFDA) and the Marginal Farmers and Agricultural Labourers (MFAL) Agencies were included in the Central Sector in the Fourth Five Year Plan (1974—78) with the specific objective of ameliorating the economic conditions of small I marginal farmers agricultural labourers in the country and to bring them into the mainstream of economic development. A sum of Rs. 103 crores was allocated for this purpose in the Fourth Plan. The Schemes were introduced gradually on a pilot basis from 1970-71 onwards in certain selected areas of the country. It was then envisaged that the experience gained from them would be useful for formulating programmes for a more extensive coverage. Since these Schemes affected the core of the Indian peasantry, their working was of considerable interest. Consequently, in 1973 the Programme Evaluation Organisation of the Planning Commission was asked to undertake their evaluation.
Programme Evaluation Organisation Planning Commission Government of India